Desulfotomaculum spp. and related gram-positive sulfate-reducing bacteria in deep subsurface environments - Aullo, Thomas; Ranchou-Peyruse, Anthony; Ollivier, Bernard; Magot, Michel (Frontiers in Microbiology, 2013)
Gram-positive spore-forming sulfate reducers and particularly members of the genus Desulfotomaculum are commonly found in the subsurface biosphere by culture based and molecular approaches. Due to their metabolic versatility and their ability to persist as endospores. Desulfotomaculum spp. are well-adapted for colonizing environments through a slow sedimentation process. Because of their ability to grow autotrophically (H2/CO2) and produce sulfide or acetate, these microorganisms may play key roles in deep lithoautotrophic microbial communities. Available data about Desulfotomaculum spp. and related species from studies carried out from deep freshwater lakes, marine sediments, oligotrophic and organic rich deep geological settings are discussed in this review.